Succession of Regional Heads Based on Kinship Relations Judging Concept of the Pancasila Legal State - Muslikhah, Umi; Chaidir, Ellydar; Sundari, Rini Irianty (Jurnal Ius Constituendum, 2024)
This research aims to examine in depth the existence of succession for Regional Heads using kinship relations in terms of the concept of the rule of law and formulate the implications of succession for Regional Heads based on kinship relations for the implementation of government duties in the region in the context of the rule of law. Indonesia, as stated in its constitution, adheres to the concept of a rule of law, this is attached to Article 1 paragraph (3) of the 1945 Constitution "Indonesia is a rule of law". One indicator of the application of the concept of the rule of law in a sovereign state is the limitation of power in administering the state. The problem studied in this research is related to how the succession of Regional Heads is related to kinship relations in terms of the concept of the rule of law. The research method used in this research is normative juridical, where the author examines through literature study and analyzes based on various relevant literature. Succession of Regional Heads based on kinship relations in Indonesia has recently become a disturbing phenomenon. As an effort to limit the existence of dynastic politics, this has been done by issuing "Law Number 8 of 2015 concerning Amendments to Law Number 1 of 2015 concerning the Determination of PERPPU Number 1 of 2014 concerning the Election of Governors, Regents and Mayors, especially in Article 7 letter r" However, this provision was canceled by the Constitutional Court with the issuance of "Constitutional Court Decision Number 33/PUU-XIII/2015". So, the absence of regulations that provide restrictions on this phenomenon has caused the succession of Regional Heads based on kinship relations to become a bad precedent in state administration Rampant updates to this research are expected by the government and the DPR to issue regulations that place restrictions on incumbents being involved in conflicts of interest in the succession of regional heads who have kinship relationships